2004
DOI: 10.1016/j.orthres.2004.01.005
|View full text |Cite
|
Sign up to set email alerts
|

The use of OP‐1 in femoral impaction grafting in a sheep model

Abstract: The aim of this pilot study was to examine bone graft incorporation in femurs impacted with allograft bone alone (control group) or with allograft containing the bone morphogenetic protein OP-I (BMP-7) (OP-1 group) in a sheep model of cemented hemiarthroplasty. Two sheep in each group were sacrificed at 6, 18 and 26 weeks. Successful bone graft incorporation was evident in both groups by six weeks but in the OP-I group, there had been more extensive resorption of the graft. There was one case of excessive stem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
39
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 30 publications
(13 reference statements)
2
39
0
Order By: Relevance
“…29 Additionally, a number of other studies have used the sheep model to study impaction grafting with calcium phosphate bone substitute materials 22 and with BMP added to the allograft. 23 Further, a telemetry study using strain gauges attached to the femoral neck of the implant showed that the magnitude and direction of the force across the hip joint in sheep is comparable to those in humans. 30 We have also demonstrated in this ovine model that the stem at the time of insertion is not in contact with the endosteal cortex, but is separated from host bone by a layer of allograft.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…29 Additionally, a number of other studies have used the sheep model to study impaction grafting with calcium phosphate bone substitute materials 22 and with BMP added to the allograft. 23 Further, a telemetry study using strain gauges attached to the femoral neck of the implant showed that the magnitude and direction of the force across the hip joint in sheep is comparable to those in humans. 30 We have also demonstrated in this ovine model that the stem at the time of insertion is not in contact with the endosteal cortex, but is separated from host bone by a layer of allograft.…”
mentioning
confidence: 95%
“…[19][20][21] Ovine hip hemiarthroplasty models have previously been used to investigate impaction grafting using bone substitutes 22 and OP-1. 23 The purpose of this study is to test the hypothesis that autologous MSCs mixed with allograft, impacted into the femoral cavity in revision surgery, can generate more new bone compared to allograft only.…”
mentioning
confidence: 99%
“…Inflammation and swelling were transient and not observed unless used under the skin, in patients operated for distal radial osteotomies and treated with BMP7 where metaphyseal bone is predominantly composed of bone marrow and mesenchymal stem cells, resulting in bone resorption and skin rash [65]. Also, when used in preclinical studies within the bone medullary canal, a pronounced bone resorption has been observed [66]. When a BMP2 device was used in patients for the lower lumbar spine fusion the complications included an autonomic plexus injury, retrograde ejaculation and heterotopic ossification [55-57, 59, 61].…”
Section: Issues Related To Bone Devices Containing Bmp2 and Bmp7mentioning
confidence: 99%
“…While resorption takes place endostealy, forming an intramedullar "halo" [66], in parallel, new bone tissue is formed outside the bone cavity to biomechanically support the broken bone ends (Fig. 3).…”
Section: Clinical Testing Of Bmp2 and -7 Revisedmentioning
confidence: 99%
“…That study found that the fused femoral impaction graft constructs were much more stable than the unfused graft constructs at the proximal stem location, but that MCB fusion had a much smaller effect on distal stem stability. This implied that most of the opportunity to increase impaction graft femoral stem stability was proximal, and therefore that steps to enhance MCB fusion -for example, using biologically active factors such as bone morphogenic proteins [11][12][13][14][15][16] -might be most effectively focused proximally.…”
Section: Introductionmentioning
confidence: 99%